EFEKTIFITAS PERAN OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN PROVINSI KEPULAUAN RIAU SEBAGAI LEMBAGA PENGAWAS PELAYANAN PUBLIK DI KOTA BATAM - Winsherly Tan (JCH (Jurnal Cendekia Hukum), 2020)
It is hoped that the presence of the Ombudsman of the Republic of Indonesia is able to serve the delivery of public services for the realization of state and government administration that is effective and efficient, honest, clean, open, and free from corruption, collusion and nepotism. This purpose is to analyze the problem factors and provide solutions to solve the problems of investigating the problems of the Ombudsman of the Republic of Indonesia Representatives of the Riau Islands Province in completing reports and preventing maladministration in Batam City. Legal Research Methods The results of observations, interviews and questionnaires as the main data source and literature study as a source of supporting data showed that the supervision of the Ombudsman of the Republic of Indonesia Representatives of the Riau Islands Province in Batam City has not been effective. The problem factors for the Ombudsman of the Republic of Indonesia Representatives of the Riau Islands Province in public services in Batam City, namely less than the budget, absence of reports, legal uncertainty, lack of support from public service providers, Ombudsman coordination and collaboration with public service providers, and public awareness. Based on these problems, the suggestion from the researcher is a recommendation so that the duties and functions of the Ombudsman run more effectively in accordance with the mandate of the Law, namely: with the revision of the UUORI and implementing regulations for legal certainty, increasing the budget and quality of the Indonesian Ombudsman HR Representatives of the Riau Islands Province , collaborating with public service providers.